Talent Development for the Twenty‐First Century: Boosting Engagement, Innovation, and Returns. Issue 70 (6th September 2013) - Maruska, Don; Perry, Jay
Abstract: According to Maruska and Perry, talent development "remains mired in nineteenth‐century top‐down thinking." People should take charge of their own development, an outcome that leaders should welcome. A seven‐point manifesto is provided, with the areas of using untapped talents and opportunities, accessing hopes to drive better results, becoming talent catalysts for one another, tapping into abundant resources, using time creatively and productively, creating a self‐organizing culture that leads to fulfillment, and using the "See one, do one, teach one" approach. Hope "can be a practical and powerful way to tap the passion, energy, and creativity that lie within us, " the authors write.